Developing Adaptive Business Strategies Using the SWOT Matrix: a Case Study of PT Tri Adi Bersama (ANTERAJA) - Rifqi Kusumah , Evan (Journal Research of Social Science, Economics, and Management, 2025)
The growth of e-commerce in Indonesia continues to drive the increasing need for last-mile logistics services that demand speed, accuracy, and operational transparency. This study aims to formulate an adaptive strategy for PT Tri Adi Bersama (Anteraja) through a SWOT analysis approach that is quantified using IFAS, EFAS, and SPACE Matrices. The research method used was descriptive quantitative with a Likert scale questionnaire instrument (1–5) based on 12 SWOT indicators (3 Strengths, 3 Weaknesses, 3 Opportunities, and 3 Threats). A total of 255 respondents participated in this study, consisting of 63 internal respondents and 192 external respondents who were selected through purposive sampling techniques. The results of data processing showed an IFAS score of 0.35, which indicates that Anteraja's internal strengths are more dominant than its weaknesses. Meanwhile, an EFAS score of 0.04 indicates a slightly greater external opportunity than a threat. The combination of these two values places Anteraja's strategic position in Quadrant I (Aggressive) in the SPACE Matrix, which reflects the company's position in a situation that supports growth and expansion. Based on these findings, the recommended adaptive strategy focuses on utilizing internal strengths and external opportunities, such as strengthening service digitization, expanding distribution networks, developing fast services (same-day/instant), and optimizing technology-based services and fulfillment. These findings are expected to be a reference for companies in formulating business strategies that are more responsive to the dynamics of the digital logistics industry.